John Paul Jones : father of the American Navy - Haugen, Brenda (Compass Point Books, 2005)
Chronicles the life and career of the "Father of the American Navy," John Paul Jones and traces his childhood in Scotland, his years as an apprentice sailor and captain of his own ship, and involvement in the American War for Independence.